Avaliação da qualidade da assistência prestada pela fonoaudiologia na estratégia de saúde da família na zona urbana de Sobral- CE - Zanin, Loíse Elena (2014)
The insertion of speech therapy in the Family Health Strategy (FHS) is somewhat new and studies in this field are still scarce. In the light of this, our objective was to identify, from national and international literature, the state of the question on the insertion and performance of speech therapy in FHS. For this purpose, we conducted a survey in the Virtual Health Library (VHL), for articles published between 1993 and 2013, being in free access periodicals or not. Also, we performed a regional survey on scientific production by speech therapists who worked in FHS in the city of Sobral, Ceará. The first investigation occurred, in loco, in the library at the Family Health Training School ‘Visconde de Sabóia’ and the second investigation was conducted by means of bibliographic survey of the SANARE journal, in the 1999-2013 period, in the online periodicals, with all the editions of the journal being analyzed, totaling 22 editions. From the study, it was possible to see that the deficiency in the training of the speech therapist for work in FHS is one of the main limiting factors for the insertion and performance of these professionals in this scenario; it was evident that few publications address the theme; the studies identified many challenges for the category of speech therapy in the consolidation of their work in FHS. Nevertheless, it was possible to acknowledge that the work of speech therapy, together with the community, promoted quality care which provided more quality of life and health for these people.